The Negative Effects of Political Buzzers on People's Communication Intelligence: A Case Study of the 2014–2024 Era in Indonesia - Iskandarsyah Siregar (Britain International for Academic Research (BIAR-Publisher), 2025)
This study investigates the adverse impact of political buzzers on communication intelligence within Indonesian society during the 2014–2024 period. Political buzzers, typically anonymous digital actors affiliated with political elites, have emerged as powerful manipulators of public discourse through disinformation, emotional provocation, and identity-based polarization. Utilizing a qualitative case study methodology, this research employs critical discourse analysis, document analysis, and semi-structured interviews to explore how sustained exposure to buzzer-driven content degrades critical thinking, discourages dialogical tolerance, and undermines the epistemic foundations necessary for democratic engagement. The findings demonstrate that buzzers deploy binary framing, fabricate consensus, and target dissenters with delegitimizing rhetoric, resulting in weakened public reasoning and increased cynicism. These effects are unevenly distributed across regions and demographics: while urban citizens exhibit media fatigue and withdrawal, rural populations remain more susceptible to disinformation. The study situates these dynamics within broader theoretical frameworks on communicative rationality and network propaganda, extending the discussion to include the cognitive and ethical dimensions of political discourse manipulation. This research contributes to interdisciplinary scholarship on digital politics and democratic resilience by foregrounding the concept of communication intelligence—an underexplored but essential faculty for informed participation in contemporary democracies. It concludes with a call for structural and cultural reforms, including the institutionalization of media literacy, platform regulation, the promotion of ethical digital norms, and the strengthening of civil society dialogue forums. These measures are imperative to counteract the corrosive influence of political buzzers and to restore a communication environment conducive to rational, ethical, and inclusive democratic deliberation.